Antonio Dias - Dias, Antonio; Duarte, Paulo Sergio; Oliva, Achille Bonito; Pradilla, Ileana (Associacao Para O Patronato Contemporaneo APC, Sao Paulo, 2015)
Antonio Dias serves as a monumental compendium that surveys the Brazilian artist$1 (Bs almost 50-year career. Edited and designed by Dias (born 1944), the volume moves through the many phases of his varied practice, from his early experimentation at age 19 with visual representations of protest--before the 1964 military coup and at Brazil$1 (Bs political and social climax--to his conceptual production in Milan, his early film work, his works on paper developed in Nepal and the painting practice that has continued throughout his life. One of Brazil$1 (Bs most versatile artists, Dias creates work that transcends borders and nationalities--as he himself states, having worked in Rio, Milan and Paris, "anywhere is my land"--and yet, few books are available on him in English. This hardcover volume, with over 400 images, changes that, offering an introduction to a canonical Brazilian artist.s
English
Keywords: N8350-8356 Art as a profession. Artists; Brazil